ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUCT UNCERTAINTY YANG DIMEDIASI OLEH SELLER UNCERTAINTY PADA SOCIAL COMMERCE - Ayu Nanda Amalia; Soepatini Soepatini (LP2M Universitas Bina Bangsa, 2024)
This study examines the analysis of factors that affect product uncertainty mediated by seller uncertainty in social commerce. The population in this study were individuals who had an online shopping experience through social media platforms (Facebook and Instagram). The sample of this study was 203 respondents. Structured Equation Modeling (SEM) is the research methodology used in this study. Applications such as SmartPLS 3.0 are used in data processing. The result of this study is that Seller uncertainty is negatively and insignificantly affected by return policy leniency. Product uncertainty is positively and significantly influenced by the variables return policy leniency, information quality, seller reputation, and seller uncertainty. Seller uncertainty is positively and significantly influenced by information quality, seller reputation, and the number of positive comments. Product uncertainty is positively and insignificantly influenced by the number of positive comments. Seller uncertainty is negatively and insignificantly affected by seller popularity. Product uncertainty is negatively and significantly influenced by Seller popularity. Return policy leniency and seller popularity have a negative and insignificant effect on product uncertainty mediated by seller uncertainty. Information quality, seller reputation, and the number of positive comments have a positive and significant effect on product uncertainty mediated by seller uncertainty